AB0298 Treat to Target (T2T) in Rheumatoid Arthritis – a Single Center Analysis. (9th June 2015) - Mohd Jamid, N.; Shahril, N.S.; Rajalingam, S.; Hussein, H.
Abstract : Background: The management of Rheumatoid Arthritis (RA) underwent a paradigm shift in the last decade. The development of composite measures and structured management aiming for a treatment target, the early institution of Disease Modifying Anti Rheumatic Drugs (DMARDs) and the availability of new medications have led to less joint damage and better physical function. Thus in 2010, the T2T expert committee developed a set of recommendations for achieving optimal therapeutic outcomes in RA. Objectives: To audit on the routine care of RA patients in Rheumatology Clinic, Putrajaya Hospital in line with the EULAR recommendations on treating RA to target. The audit was aimed to look at the followings: The percentage of patients achieving state of remission and low disease activity (LDA) at 2 years of follow-up. The duration of remission/LDA maintained in those who achieved the target. The utilization of DAS28 score, HAQ-DI and x-rays in the decision to adjust patient's management. The frequency of follow-up in the first 2 years of RA diagnosis. The documentation of discussions on treatment decision with patients. Disease activity at current follow-up. Methods: Retrospective cross-sectional analysis involving patients who attended the Rheumatology Clinic, Putrajaya Hospital from September 2013 to February 2014, who was diagnosed with RA in our centre and have at least two years follow-up data. Their electronic medical records were reviewed for data collection. Results: Seventy-two patients who met the inclusion criteria were selected. The median age was 51 year old (IQR:20-80) and median duration of RA was 5 years (IQR:2-13). Eighty nine percent were female and eleven percent were male. The Rheumatoid factor was positive in 62%. The ACPA was not available in 43.8%. In those who had their ACPA status known, 60% were positive. At 2 years of follow-up, 42% achieved remission, while 48% achieved LDA. The median duration of these state of disease activity maintained was 14 months (IQR:2-88). In 79% of patients, DAS28 was calculated at least once during the first 2 years of follow-up. HAQ-DI was not done routinely in our patients. X-rays were done for all patients at their first visit with 64% of patients had their x-rays repeated during subsequent visits of at least 1 year. Ninety percent of patients were seen every one to three monthly in the first two years of diagnosis with median frequency of 8 weeks (IQR:4-16). In all patients, the decision for choice of treatment is shared between the patient and the attending practitioner. At current follow-up, 71% had their disease in remission, 15% in LDA and 14% in moderate to high disease activity state. Median DAS28CRP was 2.05 (IQR:0.97-6.22) and HAQ-DI was 0.5 (IQR:0.000-2.375). At current visit, 45.3% were on combination synthetic DMARDs, 36.1% were on synthetic DMARDs monotherapy, 9.7% were on combination synthetic and biological DMARDs and 8.3% were not on DMARDs due to either adverse events or intolerance. Those who were in remission and LDA at current follow-up tended to be Rheumatoid factor negative and of older age group. Conclusions: The management of RA in Rheumatology Clinic, Putrajaya Hospital is in line with EULAR recommendations and target of treatment is achievable in majority of patients. References: Treating Rheumatoid Arthritis To Target: Recommendations Of An International Task Force. Josef S Smollen, Daniel Aletha, Johannes WJ Bijlsma, et al. Ann Rheum Dis 2010;69:631-637. Disclosure of Interest: None declared